Effects of a supervised exercise program in addition to electrical stimulation or kinesio taping in low back pain: a randomized controlled trial - Aguilar-Ferrándiz, María Encarnación; Matarán-Peñarrocha, Guillermo A.; Tapia-Haro, Rosa María; Castellote-Caballero, Yolanda; Martí-García, Celia; Castro-Sánchez, Adelaida María (Springer Nature, 2022)
Chronic low back pain it is one of the most common health problems worldwide. Usually is accompanied by a complex set of symptoms and generates significant direct and indirect socioeconomic and health costs. From a therapeutic point of view, there are a wide variety of methods to address the treatment of this pathology, however, these therapies have not been shown definitive efficacy. To investigate the effect of a mixed treatment with exercise and electrical stimulation versus exercise and kinesio taping in patients with non-specific chronic low back pain. A total of 58 patients participated in this single-blinded randomised clinical trial. Participants were assigned to the exercises- kinesio taping group, or exercises- analgesic current group, both received 12 treatment sessions. Disability, fear of movement, anxiety, depression, sleeps quality, pain, lower limb mechanosensitivity and pressure-pain thresholds were recorded at baseline and after 4 weeks of treatment. The 2 × 2 mixed analysis of covariance test showed statistically significant differences between groups for pain (P = 0.046). Pair-wise comparisons with baseline demonstrated significant differences for both groups in pain (P ≤ 0.001), disability (P ≤ 0.001), pressure-pain thresholds (P ≤ 0.044), lower limb mechanosensitivity, (P ≤ 0.047), anxiety (P ≤ 0.001), depression (P ≤ 0.001) and sleep quality (P ≤ 0.010). Patients with chronic low back pain who received a combined treatment of exercises and kinesio taping or analgesic current showed an improvement in pain, disability, anxiety, depression and sleep pattern. Moreover, exercises combined with electrotherapy produces greater improvements over these variables.
Keywords: Lumbalgia; Low back pain; Chronic Disease; Kinesio Taping; Transcutaneous electric nerve stimulation; Randomised clinical trial